Water - Day, Trevor; Cockburn, Dave (London ; New York : DK, 2007)
Full-color photographs and text explore water; covering marine life, weather, clouds, floods and droughts, global warming, rivers, oceans, tides, currents, and other related topics.
Includes index.
7.4
5-8.
5-8
Keywords: Water -- Juvenile literature; Water; Water